TURBO PASCAL END TO SUPPORT APPLICATION EXAM USING COMPUTER COURSE IN BAHASA BEKASI PYRAMID - Wiwiek Pujiningsih; Ire Puspa Wardhani,SKom MMSI (Jurnal Sistem Informasi, 2000)
Application of the test using the computer facilities in the implementationmembaerikan exam. Easiness obtained by the teachers and students among others toimprove the effectiveness and efficiency in terms of time and cost.